Human Motor Neurons With SOD1-G93A Mutation Generated From CRISPR/Cas9 Gene-Edited iPSCs Develop Pathological Features of Amyotrophic Lateral Sclerosis - Kim, Byung Woo; Ryu, Jiwon; Jeong, Ye Eun; Kim, Juhyun; Martin, Lee J. (Frontiers in Cellular Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by gradual degeneration and elimination of motor neurons (MNs) in the motor cortex and spinal cord. Some familial forms of ALS are caused by genetic mutations in superoxide dismutase 1 (SOD1) but the mechanisms driving MN disease are unclear. Identifying the naturally occurring pathology and understanding how this mutant SOD1 can affect MNs in a valid and reliable human cell model remains to be established. Here, using CRISPR/Cas9 genome editing system and human induced pluripotent stem cells (iPSCs), we generated highly pure, iPSC-derived MNs with a SOD1-G93A missense mutation. With the wild-type cell line serving as an isogenic control and MNs from a patient-derived iPSC line with an SOD1-A4V mutation as a comparator, we identified pathological phenotypes relevant to ALS. The mutant MNs accumulated misfolded and aggregated forms of SOD1 in cell bodies and processes, including axons. They also developed distinctive axonal pathologies. Mutants had axonal swellings with shorter axon length and less numbers of branch points. Moreover, structural and molecular abnormalities in presynaptic and postsynaptic size and density were found in the mutants. Finally, functional studies with microelectrode array (MEA) demonstrated that the individual mutant MNs exhibited decreased number of spikes and diminished network bursting, but increased burst duration. Taken together, we identified spontaneous disease phenotypes relevant to ALS in mutant SOD1 MNs from genome-edited and patient-derived iPSCs. Our findings demonstrate that SOD1 mutations in human MNs cause cell-autonomous proteinopathy, axonopathy, synaptic pathology, and aberrant neurotransmission.